The musical imagination of Andrei Platonov - Bullock, P (W. S. Maney & Son. Ltd, 2004)
This article considers ideas about the nature and function of music, instances of musical performance, and references to various pieces of music in the works of Andrei Platonov. For a writer often seen as a self-taught, idiosyncratic genius, Platonov displays an attitude to music that is surprisingly learned; by considering this neglected subject, conclusions are drawn about Platonov's aesthetics. The article deals with most of Platonov's major works and falls broadly into two halves. The first begins with Platonov's indebtedness to Symbolist ideas of music as the foremost metaphor for idealism. It goes on to consider how the utopian imagination is often configured as the attempt to hear an almost imperceptible music. It also suggests that in Chevengur, music expresses both the utopian search for primal oneness and the hermeneutic impossibility of the discourses that structure utopia. The second half of the article is concerned with Platonov's representation of music of the Soviet state in works such as Kotlovan, Iuvenil'noe more, and Schastlivaia Moskva, arguing that the almost imperceptible music that had previously obsessed Platonov was now tragically overlaid with the noisy symphonism that was to become Socialist Realism. The article concludes by considering several parallels between Platonov and Shostakovich in the mid-1930s.